(untitled) (Journal of Asian Development Studies, 2025)
The rapid pivot to online learning during COVID-19 reconfigured adolescents’ everyday ecologies in ways that reverberated across mental health. This qualitative, ecologically framed study examined how platformed schooling shaped students’ emotional well-being, motivation, and sense of belonging. Using semi-structured interviews, reflective prompts, and open-ended survey items analyzed through thematic coding, we identified five recurrent outcomes: (1) emotional disengagement—flattened motivation and difficulty initiating schoolwork; (2) social anxiety and isolation—loss of informal peer contact and heightened self-consciousness on camera; (3) digital dependence and screen fatigue—concentration drains and sleep disruption linked to continuous device use; (4) inequities in access—unstable connectivity, shared devices, and crowded homes intensifying strain for lower-SES students; and (5) thin school-based support—limited, uneven contact with counselors and inconsistent teacher outreach. Protective factors included steady peer ties, responsive teachers, predictable routines, and parental scaffolding that translated platform tasks into manageable steps. Interpreted through Bronfenbrenner’s ecological systems theory, these patterns reflect multi-level disruptions (micro- to macro-systems) rather than individual deficits, clarifying why burdens are clustered among resource-constrained households. The study recommends incorporating mental-health literacy into curricula, implementing routine brief screenings with referral pathways, enhancing teacher capacity for socio-emotional support, and implementing digital equity measures (low-data resources, loaner devices) to buffer future disruptions and rebuild a sense of belonging.